2020
DOI: 10.1080/1828051x.2020.1760740
|View full text |Cite
|
Sign up to set email alerts
|

Response of Japanese quails (Coturnix coturnix japonica) to dietary inclusion of Moringa oleifera essential oil under heat stress condition

Abstract: The present study was aimed at investigating the effects of the dietary use of different doses of Moringa oleifera essential oil (MOEO) on performance parameters, internal organ weights and meat quality in Japanese quails (Coturnix coturnix japonica) exposed to Heat Stress (HS). For this purpose, 320 male day-old quail chicks were used. Seven days of preliminary (physical exercise) and a 35-day fattening period were applied. The animals were divided into 8 groups, each including 40 animals according to tempara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Reports that dietary moringa essential oil improves growth performance in stressed poultry [ 2 , 28 , 29 ] supports the clams of this study. Similarly, Daramola et al [ 30 ] has reported that moringa leaf meal can be used as feed additive to enhance performance and antioxidant status of laying birds.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Reports that dietary moringa essential oil improves growth performance in stressed poultry [ 2 , 28 , 29 ] supports the clams of this study. Similarly, Daramola et al [ 30 ] has reported that moringa leaf meal can be used as feed additive to enhance performance and antioxidant status of laying birds.…”
Section: Discussionsupporting
confidence: 89%
“…The shock of heat stress on poultry birds is a significant predicament and a cause for economic dispossession in the poultry industry, hence it exerts a detrimental influence on physiological responses like immunity, oxidative stress, and intestinal and muscular functions [1]. Poultry birds enjoys to be raised under situations of minor energy requirement for thermoregulation purposes and ultimate net energy available for production goal, otherwise poultry will be under stress [2]. Reports of Abreu and Abreu [3] and Bueno et al [4] stated that the actual temperature varies from 32℃ to 35℃ (1st week), 23℃-32℃ (2nd and 5th week), and 20℃ (6th week) and relative humidity ranging from 60%-70%, which are difficult conditions to keep in the tropics.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a number of authors have reported an improved feed intake in response to different doses and forms of M. oleifera [ 65 , 66 , 67 ]. According to Zanu et al [ 88 ], the addition of Moringa meal reduced feed conversion efficiency considerably.…”
Section: Feed Intake and Efficiencymentioning
confidence: 99%
“…Heat stress decreased nuclei per millimetre of muscle fibre in fast-growing Japanese quail but increased mean muscle fibre diameter. Authors reported varied results on muscle colour: (Tekce et al, 2020a) reported lower lightness L* values but subsequently reported no changes in values (Tekce et al, 2020b). The remaining authors (Imik et al, 2010;Jimenez & De Jesus, 2021;Jimenez et al, 2018;Kaplan & Koksal, 2021).…”
Section: Review Findingsmentioning
confidence: 99%